Development of a Real-Time Multiplayer Web-Based Mathematical Puzzle Game for Geometric Reflection Learning Using WebSocket - Fathan Mohamad; Rahmat Deddy Riyanto Dako; Ulfatun Nadifa; Wahab Musa; Syahrir Abdussamad; Bambang Panji Asmara (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
Mathematics learning at the senior secondary level often faces challenges related to student engagement, heterogeneous comprehension levels, and the absence of interactive feedback mechanisms. This study develops and evaluates a web-based mathematical puzzle game named